Relação monômero e dímero em pele sadia em função da concentração do azul de metileno e seu consequente efeito histológico associado a terapia fotodinâmica - Gomes, Mariana Teixeira (2016)
Background: Recently, the methylene blue photosensitizer (MB) has been used in photodynamic therapy (PDT), but the concentrations and its mode of application are not well established in the literature, which leads to a compromised efficacy of PDT. Objective: Using the absorbance ratio between monomer and dimer, to infer about the type of mechanism of PDT (if type I or II) in intact animal model skin in vivo as a function of different concentrations of the MB photosensitizer and its consequent effects on tissue morphology and organization of collagen fibers. Methods: Twenty-five Wistar rats, equally distributed in 5 groups with different concentrations of MB (0.01%, 0.1%, 1%, 2%) and 0.9% NaCl saline, which was used as solvent. Injection of MB was performed via intradermal at 8-point of healthy skin in the amount of 0.1 mL per point. Four of the points were irradiated with λ= 660 nm, P= 100 mW, I= 510 mW/cm2, E= 4 J, ER= 20 J/cm2 for 40 s, and the other four points received no irradiation. Also, an extra point, without any intervention, was studied as reference. Absorption spectra were collected at 3 different times and euthanasia occurred after 2 or 4 hours from irradiation. The collected material was processed to investigate the inflammatory response and the ordering of the collagen fibers. Results and Conclusions: After 2 hours of irradiation, there was a higher monomer/dimer ratio with 1% MB. After 4 hours, the highest ratios were observed at the concentration of 2%. The mechanism predominantly involved was type II. The inflammatory process was higher in the lower concentrations of MB when irradiated. The arrangement of the collagen fibers was not influenced by the different concentrations of MB.